The Effect Of Performance Feedback System And Work-Life Balance Initiative On Employe Retention In Cikarang Manufacturing Industry Company - Prasetyo, Prasetyo; Triastutik, Ananda Hesti (Growth: Journal Management and Business, 2024)
This study analyzes the influence of performance feedback systems and work-life balance initiatives on employee retention in the Cikarang manufacturing sector. Employee retention is a crucial issue, especially with the high turnover rate influenced by employee expectations, especially from the Millennial and Gen Z generations. The results show that this system increases job satisfaction and employee commitment, thereby reducing turnover. Additionally, work-life balance initiatives, such as flexible work schedules and mental health support, are an important factor in increasing employee loyalty. This research confirms that the integration of feedback systems and work-life balance strategies significantly contributes to creating a supportive work environment and organizational sustainability. These findings show the importance of implementing these strategies in effective human resource management.